PERAN ORANGTUA DALAM MENCEGAH PERILAKU KEKERASAN SEKSUAL REMAJA KOTA PADANG (Perspektif Komunikasi Keluarga) - Fitri Al Shibi; Ernita Arif; Rahmi Surya Dewi (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2020)
The family is the closest environment to teenagers, where the family is the first place for teenagers to socialize outside the home. Whereas adolescents are the most transitional period that can influence their teenage sexual behaviour. . Where there are currently many sections that occur during adulthood. This research was conducted with qualitative methods, namely in-depth interviews and observations, conclusions can be obtained. The results of this study discuss the communication between parents and children is the most important thing for children who are victims of sexual violence, besides religious education, early sexual understanding and moral are also very much needed in establishing communication within a family.